Perbedaan Penangkapan 99mTc-Pyrophosphate vs 99mTc- Methylenediphosphate dalam Mendeteksi Amyloidosis Jantung; Pengalaman Pertama di RSUP Hasan Sadikin - Hadi Marzuki; Erwin A Soeriadi; Astri Astuti; Hendra Budiawan; Achmad Hussein S Kartamihardja (Universitas Kristen Maranatha, 2022)
Cardiac amyloidosis (CA) is a disorder caused by deposits of insoluble fibrils in the myocardium and an underdiagnosed cause of heart failure. Immunoglobulin Light Chain-Associated Amyloid (AL) and Amyloidosis Transthyretin-related (ATTR) are the two protein precursors that most commonly cause cardiac amyloidosis. It is important to distinguish between these two types of amyloidosis because the treatment and prognosis of each types is different. Recent advances in cardiac radionuclide imaging, in particular using bone-seeking agents such as 99mTc-Pyrophosphate (PYP) and 99mTc-Methylenediphosphate (MDP), can differentiate AL from ATTR. This study aimed was to investigate the uptake characteristic of both tracers in CA. Three patients with suspected of having cardiac amyloidosis underwent two cardiac radionuclide imaging examinations using those two different radiopharmaceuticals. The cardiac images were analyzed quantitatively and semi-quantitatively based on ASNC (American Society of Nuclear Medicine) criteria. Cardiac radioactivity uptake of 99mTc-PYP was better from those of 99mTc-MDP based on quantitative as well as semi-quantitative (visual assessment). Keywords: cardiac amyloidosis; cardiac imaging; 99mTc-PYP; 99mTc-MDP